2000
DOI: 10.1021/jf0003911
|View full text |Cite
|
Sign up to set email alerts
|

Caseins and Casein Hydrolysates. 2. Antioxidative Properties and Relevance to Lipoxygenase Inhibition

Abstract: The antioxidant activity of caseins and casein-derived peptides was evaluated by using three free radical producing reactions-the lipoxygenase- and AAPH-catalyzed oxidation of linoleic acid and the hemoglobin-catalyzed oxidation of linoleic acid hydroperoxide. Caseins and casein-derived peptides were able to inhibit enzymatic and nonenzymatic lipid peroxidation, suggesting they were preferred targets for the free radical intermediates. The antioxidative feature was not lost with the dephosphorylation or the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
199
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(208 citation statements)
references
References 44 publications
(51 reference statements)
7
199
0
2
Order By: Relevance
“…Several studies reported antioxidant effects of both casein and whey hydrolysates produced by different enzymes (80,81) . Many tripeptides (other than LTP, for example, Xaa -Xaa-Trp/Tyr, Tyr-His-Tyr) that show high scavenging activity and strong synergistic effects with phenolic antioxidants have been identified in milk (82) .…”
Section: Putative Mechanisms Underlying the Impact Of Milk Peptides Omentioning
confidence: 99%
“…Several studies reported antioxidant effects of both casein and whey hydrolysates produced by different enzymes (80,81) . Many tripeptides (other than LTP, for example, Xaa -Xaa-Trp/Tyr, Tyr-His-Tyr) that show high scavenging activity and strong synergistic effects with phenolic antioxidants have been identified in milk (82) .…”
Section: Putative Mechanisms Underlying the Impact Of Milk Peptides Omentioning
confidence: 99%
“…Much physiological damage may be directly imputable to the hydroxyl radical, because it is highly reactive, and so many hydroxyl radicals produced in vivo react at or close to their site of formation. The biochemical literature is full of claims that reactive species are involved in different diseases (Southorn & Powis, 1988).Many proteins have been reported to have antioxidant activities against the peroxidation of lipids or fatty acids upon hydrolysis (Rival et al, 2001, Suetsuna, 2000Chen et al, 1998;Hattori et al, 1998;Bishov & Henick, 1972). Gluten has a unique amino acid composition, with Glu/Gln and Pro accounting for more than 50% of the amino acid residues.…”
mentioning
confidence: 99%
“…This could result from the binding of iron to the phosphopeptide, limiting both initiation of the reaction and breakage of the hydroperoxides. Free radical scavenging by the peptides, or reactions of peroxidizing lipids with amino groups of the protein hydrolysate, causing losses in reacting amino acids, cannot be excluded [23,52]. Loss of methionine during storage of casein and of lysyl, tryptophanyl and histidyl residues of whey proteins were observed previously in the presence of oxidizing methyl linoleate [7,45,55].…”
Section: Discussionmentioning
confidence: 94%
“…The antioxidant activity of milk proteins such as lactoferrin, transferrin and caseins has been demonstrated in various systems [2,25,46,49,54,56]. Casein hydrolysates and caseinderived peptides have been shown to inhibit enzymatic and non-enzymatic lipid peroxidation [52]; caseinophosphopeptides were demonstrated to exhibit antioxidant properties in oil-in-water emulsions [14]. Iron chelation, scavenging of free radicals, and reactions of some side-chains of amino acids with hydroperoxides or secondary oxidation products, such as malonaldehyde and other aldehydes, are the main mechanisms involved in the antioxidant activity of amino acids, peptides and proteins [12,23,24,26,33,34,44,45].…”
Section: Introductionmentioning
confidence: 99%